Lithium-ion battery and terminal device
Patent Information
- Application Number
- CN202111114223.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-09-23
AI Technical Summary
利用硅基材料SiOx作为负极可有效提升锂离子电池的能量密度,但其在首次充电嵌锂的过程中会形成不可逆的副产物氧化锂和硅酸锂,会造成电池中大量活性锂离子的损失,由此造成硅基负极电池的首效低于80%
Smart Images

Figure CN115863754B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to a lithium-ion battery and a terminal device. Background Technology
[0002] With the expansion of the electronic product market and the development of power and energy storage devices, consumers' requirements for lithium-ion batteries are constantly increasing, making the development of lithium-ion batteries with high energy density a research hotspot. Using silicon-based material SiOx as the anode can effectively improve the energy density of lithium-ion batteries. However, during the initial lithium intercalation process, irreversible byproducts lithium oxide and lithium silicate are formed, resulting in a significant loss of active lithium ions in the battery. Consequently, the initial efficiency of silicon-based anode batteries is less than 80%. To improve the initial efficiency of silicon-based anode batteries, pre-lithiation treatment is usually performed on the silicon-based anode material. Pre-lithiation of the silicon-based material results in a higher alkalinity, which easily causes the decomposition of esters in the electrolyte. This hinders the formation of fluorocarbonate films on the anode surface, and the resulting solid electrolyte interphase (SEI) film has poor stability. This leads to continuous side reactions between the silicon-based anode and the electrolyte, ultimately causing a decline in battery cycle performance. Summary of the Invention
[0003] This application provides a lithium-ion battery and terminal device to improve the cycle life of lithium-ion batteries using silicon-based materials as negative electrodes.
[0004] In a first aspect, this application provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte filled between the positive and negative electrodes. The negative electrode active material includes lithium silicon oxide (Li₂O₃). x Si y O 1+2y 1 < x ≤ 4, 1 ≤ y ≤ 4, the mass percentage of lithium silicon oxide in the negative electrode active material is a; the electrolyte includes additives, the additives include lithium salt additives, the mass percentage of lithium salt additives in the electrolyte is b; where the relationship between a and b satisfies: 0.005 ≤ b / a ≤ 0.05.
[0005] This application controls the amount of lithium salt additive added to the electrolyte based on the content of lithium silicon oxide compounds in the negative electrode active material. Adding a specific amount of lithium salt additive allows it to react with Li before the fluorocarbonate. x Si y O 1+2y Reaction, passivation of Li x Si y O 1+2y The alkaline surface strength enhances the film quality of fluorocarbonate on the negative electrode surface, effectively preventing Li... x Siy O 1+2y The alkaline surface comes into contact with the electrolyte during cycling, thereby effectively reducing Li. x Si y O 1+2y The side reaction with the electrolyte improves the cycle performance and high-temperature storage performance of lithium-ion batteries, thereby enhancing their overall performance. This lithium-ion battery uses silicon-based materials as the negative electrode and features high initial efficiency, good cycle life, and good storage performance.
[0006] In one possible implementation of this application, the mass percentage 'a' of lithium silicon oxide in the negative electrode active material ranges from 30% to 70%, in order to further optimize the initial efficiency and capacity of the lithium-ion battery.
[0007] In one possible implementation of this application, the mass percentage b of the lithium salt additive in the electrolyte ranges from 0.05% to 3%; in a preferred implementation of this application, the mass percentage b of the lithium salt additive in the electrolyte ranges from 0.1% to 2%, so that the passivation layer formed after the lithium salt reacts with the negative electrode active material is more uniform, and the passivation layer formed is more conducive to the formation of fluorocarbonate film.
[0008] In one possible implementation of this application, the lithium salt additive includes at least one of lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium difluorobis(oxalato)phosphate, or lithium difluorophosphate.
[0009] In one possible implementation of this application, the additive in the electrolyte further contains fluorocarbonate, the mass percentage of which is c in the electrolyte, and the relationship between a and c satisfies: 0.05 ≤ c / a ≤ 0.5. In another possible implementation of this application, the mass percentage c of fluorocarbonate in the electrolyte ranges from 1% to 20%. This concentration of fluorocarbonate can form a stable SEI film on the surface of the passivated negative electrode active material.
[0010] In one possible implementation of this application, the fluorocarbonate includes at least one of fluoroethylene carbonate or difluoroethylene carbonate.
[0011] In one possible implementation of this application, the electrolyte further includes an electrolyte, wherein the molar concentration of the electrolyte is 0.01 mol / L to 2.0 mol / L.
[0012] In one possible implementation of this application, the electrolyte further includes sulfur-containing ester compounds and / or nitrile compounds, wherein the mass percentage of the sulfur-containing ester compounds in the electrolyte is 1% to 5%, and the mass percentage of the nitrile compounds in the electrolyte is 2% to 6%.
[0013] Secondly, this application also provides a terminal device, including an electrical component and a lithium-ion battery provided in the first aspect of this application, wherein the lithium-ion battery is electrically connected to the electrical component to provide power to the electrical component.
[0014] In one possible embodiment of this application, the terminal device may further include a housing, in which electrical components and a lithium-ion battery may be housed.
[0015] Among them, terminal devices can be consumer electronics products such as mobile phones, tablets, power banks, laptops, and other wearable or portable electronic devices, or they can be vehicles, energy storage devices, base stations, and other equipment products.
[0016] Since the terminal device of this application includes the lithium-ion battery of the first aspect of this application, the terminal device of this application has higher safety and reliability. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the structure of a lithium-ion battery provided in an embodiment of this application;
[0018] Figure 2 The test graphs show the film formation potentials of the lithium-ion batteries corresponding to Example 1 and Comparative Example 1.
[0019] Figure 3 Elemental analysis spectra of the SEI films in Example 1 and Comparative Example 1;
[0020] Figure 4 This is a comparison graph showing the cycle performance of lithium-ion batteries in Example 9 and Comparative Example 1.
[0021] Figure label:
[0022] 10 - Positive electrode; 101 - Positive electrode current collector; 102 - Positive electrode active material; 20 - Negative electrode; 201 - Negative electrode current collector;
[0023] 202 - Negative electrode active material; 30 - Separator; 40 - Electrolyte. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this application clearer, the principle and application scenarios of the lithium-ion battery of this application will be further described in detail below with reference to the accompanying drawings.
[0025] Lithium-ion batteries are widely used in various electronic products such as mobile phones, computers, power banks, and automobiles. Therefore, performance indicators of lithium-ion batteries, such as energy density, cycle stability, and reliability, are important standards for evaluating their quality. Existing lithium-ion batteries using silicon-based materials as the negative electrode have high energy density, and after pre-lithiation, they can achieve high initial efficiency. However, compared to traditional negative electrode materials, pre-lithiation of silicon-based materials forms lithium silicon oxide compounds (Li). x Si y O 1+2y The high alkalinity of the electrolyte exacerbates side reactions between the negative electrode and the electrolyte, hindering the formation of a fluorocarbonate film on the negative electrode surface. Furthermore, the resulting SEI film exhibits poor stability, leading to decreased cycle performance of the lithium-ion battery. Additionally, the high concentration of lithium salts in existing electrolytes results in higher cell impedance, further deteriorating cycle performance and high-temperature storage capabilities.
[0026] To address the aforementioned technical problems, this application provides a lithium-ion battery. The terminology used in the following embodiments is for the purpose of describing specific embodiments only and is not intended to be limiting of this application. As used in the specification and appended claims of this application, the singular expressions “a,” “an,” “the,” “the,” and “this” are intended to also include expressions such as “one or more,” unless the context clearly indicates otherwise.
[0027] References to "one embodiment" or "some embodiments" as described in this specification mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized.
[0028] Figure 1 This application presents a schematic diagram of the structure of a lithium-ion battery according to one embodiment. (See diagram below.) Figure 1As shown, the lithium-ion battery includes a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte 40. The separator 30 is disposed between the positive electrode 10 and the negative electrode 20, and the electrolyte 40 fills the space between the positive electrode 10 and the negative electrode 20 and wets the separator 30. During charging, lithium ions are extracted from the positive electrode active material 102 of the positive electrode 10, pass through the electrolyte 40, and then insert into the negative electrode active material 202 of the negative electrode 20. During discharging, lithium ions are extracted from the negative electrode active material 202, pass through the electrolyte 40, and then insert into the positive electrode active material 102.
[0029] The following will be Figure 1 The positive electrode 10, negative electrode 20, separator 30, and electrolyte 40 of the lithium-ion battery are described in detail.
[0030] positive electrode
[0031] like Figure 1 As shown, in one embodiment of this application, the positive electrode 10 includes a positive electrode current collector 101 and a positive electrode material layer coated on the surface of the positive electrode current collector 101. In addition to the positive electrode active material 102, the positive electrode material layer may also include a certain amount of binder, conductive agent and other components.
[0032] The positive electrode current collector 101 can be a metal foil, such as copper foil, gold foil, or platinum foil. The positive electrode active material 102 can reversibly insert / deintercalate lithium ions. The positive electrode active material 102 can be, for example, lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), or lithium nickel cobalt manganese oxide (LiNiO2). 0.8 Co 0.1 Mn 0.1 Lithium nickel cobalt aluminum oxide (LiNiCoAlO2) or polyanionic lithium compounds LiM a (PO4) b (M is at least one of Ni, Co, Mn, Fe, Ti, and V, 0≤a≤5, 0≤b≤5), etc. This application does not limit the specific type of the positive electrode active material 102; any compound capable of reversibly inserting / deintercalating lithium ions is acceptable. The binder may be, for example, polyvinylidene fluoride (PVDF), and the conductive agent may be, for example, graphite, amorphous carbon, carbon nanotubes, carbon fibers, graphene, etc. The above binders and conductive agents are merely illustrative examples and are not specifically limited herein.
[0033] negative electrode
[0034] like Figure 1As shown, in one embodiment of this application, the negative electrode 20 includes a negative electrode current collector 201 and a negative electrode material layer coated on the surface of the negative electrode current collector. In addition to the negative electrode active material 202, the negative electrode material layer may also include a certain amount of binder, conductive agent and other components.
[0035] The negative electrode current collector 201 can be a metal foil, such as copper foil, gold foil, or platinum foil. The negative electrode active material 202 is a silicon-based material capable of accepting and releasing lithium ions, such as silicon suboxide (SiO2). X In the silicon suboxide, 0 < X < 2. Additionally, the negative electrode active material 202 also includes the lithium silicon oxide crystal compound Li. x Si y O 1+2y Where 1 < x ≤ 4 and 1 ≤ y ≤ 4, to ensure high initial efficiency of the lithium-ion battery. The binder can be, for example, sodium carboxymethyl cellulose, styrene-butadiene rubber, etc., and the conductive agent can be, for example, graphite, amorphous carbon, carbon nanotubes, carbon fibers, graphene, etc. The above binders and conductive agents are merely illustrative examples and are not specifically limited herein.
[0036] In one embodiment of this application, the lithium silicon oxide crystal compound Li x Si y O 1+2y The mass percentage of the negative electrode active material 202 is denoted as 'a'. In one embodiment of this application, the value of 'a' may range from 30% to 70%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%.
[0037] diaphragm
[0038] As shown in Figure 1, in a lithium-ion battery, the separator 30 blocks electrons from passing through while allowing ions to pass through. In one embodiment of this application, the separator 30 includes, but is not limited to, single-layer polypropylene (PP), single-layer polyethylene (PE), double-layer PP / PE, double-layer PP / PP, and triple-layer PP / PE / PP separators.
[0039] electrolyte
[0040] like Figure 1 As shown, in a lithium-ion battery, the electrolyte 40 is the transport medium for lithium ions during transport between the positive electrode 10 and the negative electrode 20. In one embodiment of this application, the electrolyte 40 includes an organic solvent, an electrolyte, and additives, wherein the electrolyte and additives are both dissolved in the organic solvent.
[0041] In one embodiment of this application, the organic solvent includes, but is not limited to, at least one of carbonate solvents, ether solvents, and carboxylic acid ester solvents. Carbonate solvents include, but are not limited to, dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, or propylene carbonate. Ether solvents include, but are not limited to, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, 1,2-dimethoxyethane, or diethylene glycol dimethyl ether. Carboxylic acid ester solvents include, but are not limited to, methyl formate, ethyl formate, ethyl acetate, propyl acetate, or propyl propionate.
[0042] In one embodiment of this application, the electrolyte includes, but is not limited to, LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], and Li[(C m F 2m+1 SO2)(C n F 2n+1 One or more of [SO2)N], where m and n are natural numbers. In one embodiment of the electrolyte of this application, the molar concentration of the electrolyte can be from 0.01 mol / L to 2.0 mol / L. For example, the molar concentration of the electrolyte in the electrolyte can be 0.01 mol / L, 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, or 2.0 mol / L.
[0043] In one embodiment of this application, the additives include fluorocarbonate and lithium salt additives.
[0044] In one embodiment of this application, the mass percentage of the lithium salt additive in the electrolyte is denoted as b, and the value of b can range from 0.05% to 3%. In a further embodiment of this application, the value of b can range from 0.1% to 2%. The relationship between b and a must satisfy: 0.005 ≤ K = b / a ≤ 0.05. It is understood that the values of a and b, and the calculated value of K, are subject to certain measurement and testing system errors during actual testing operations. Values within the system error range can be understood as the range defined by the embodiments of this application.
[0045] As an example, the value of K can typically, but not limitedly, be 0.005, 0.007, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.040, 0.045, 0.05, or any number between any two of the above values. These are all possible values for K. For example, K can be a value between 0.005 and 0.007, a value between 0.01 and 0.03, a value between 0.02 and 0.05, or any other number between any two values.
[0046] Additionally, as an example, the mass percentage b of the lithium salt additive in the electrolyte can be, for example, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.7%, 0.9%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.5%, 2.7%, or 3%.
[0047] In one embodiment of this application, the lithium salt additive includes, but is not limited to, at least one of lithium bis(oxalato)borate (LiBOB), lithium difluorooxalato)borate (LiDFOB), lithium difluorobis(oxalato)phosphate (LiDFOP), or lithium difluorophosphate (LiPO2F2).
[0048] In one embodiment of this application, the mass percentage of fluorocarbonate in the electrolyte is denoted as c. The value of c can range from 1% to 20%. As an example, the fluorocarbonate can be at least one of fluoroethylene carbonate (FEC) or difluoroethylene carbonate (DFEC). For example, the mass percentage c of fluorocarbonate in the electrolyte can be, for example, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, or 20%.
[0049] In one embodiment of this application, the ratio L of c and a can satisfy: 0.05≤L=c / a≤0.5.
[0050] As an example, the value of L can typically, but is not limiting, be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two of the above. These are all possible values for L. For example, L can be a value between 0.05 and 0.08, between 0.08 and 0.2, between 0.1 and 0.5, or any other value between any two of the above. It is understood that the values of a and c, and the calculated value of L, may have a certain degree of measurement and testing system error during actual testing. Values within the system error range can be understood as falling within the range defined by the embodiments of this application.
[0051] In one embodiment of this application, the electrolyte may further include sulfur-containing ester compounds. The mass percentage of the sulfur-containing ester compounds in the electrolyte may be, for example, 1% to 5%, such as, 1%, 2%, 3%, 4%, or 5%.
[0052] In one embodiment of this application, the sulfur-containing ester compounds include, but are not limited to, at least one of dimethyl sulfite, diethyl sulfite, vinyl sulfite, vinyl sulfate, methylene disulfonate, 1,3-propanesulfonate lactone, 1,4-butanesulfonate lactone, dimethyl sulfate, or diethyl sulfate.
[0053] In one embodiment of this application, the electrolyte may further include a nitrile compound. The mass percentage of the nitrile compound in the electrolyte may be, for example, 2% to 6%, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, or 6%.
[0054] In one embodiment of this application, the nitrile compounds include, but are not limited to, polynitrile compounds including at least one of butadionitrile, glutaronitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane or 1,3,6-hexanetrionitrile.
[0055] As an example, in one embodiment of this application, the preparation steps of the electrolyte include: dissolving a fully dried lithium salt in an organic solvent in an inert or closed environment, stirring and mixing it into a homogeneous solution, and then adding an additive to the solution and mixing it evenly to obtain the electrolyte of this embodiment.
[0056] As an example, an energy dispersive spectroscopy (EDS) analyzer can be used to analyze and test the negative electrode active material. The following embodiments illustrate how the composition of the electrolyte in a finished lithium-ion battery can be tested. In one embodiment of this application, the method for analyzing the composition of the electrolyte in a lithium-ion battery is as follows:
[0057] 1. Electrolyte extraction
[0058] Take the lithium-ion battery after formation or capacity testing, use a press and syringe to extract the electrolyte, put the extracted electrolyte into a sample bottle, place it in a refrigerator, and wait for testing.
[0059] 2. Quantitative testing method for lithium salt additives such as LiDFOB and LiBOB in electrolyte
[0060] 2.1 Dionex Ion Chromatography-Anionization Method
[0061] 2.1.1 Overview
[0062] Method for determining the content of lithium salts and some additives using a Dionex ion chromatograph with an acetonitrile mobile phase.
[0063] 2.1.2 Instruments and Reagents
[0064] Dionex ion chromatograph, anion detection system;
[0065] Analytical column: IP AG22 + IP AS 22 (4×250mm);
[0066] Chemical suppressor: AMMS 4mm
[0067] Analytical balance (0.0001g);
[0068] F-membrane (water and oil dual-use) (0.45μm);
[0069] 2.5mL syringe;
[0070] 0.22μm syringe-type filter membrane (water membrane);
[0071] Na₂CO₃ / NaHCO₃, 0.5 mol / L (provided by THERMO), acetonitrile (chromatographic grade)
[0072] Ultrapure water, resistivity greater than 18MΩ
[0073] Other commonly used laboratory instruments and utensils.
[0074] 2.1.3 Preparation of eluent (taking 20% acetonitrile organic phase as an example)
[0075] 1) Accurately measure 200 mL of chromatographic grade acetonitrile, add ultrapure water to accurately dilute to 1 L, shake well and set aside.
[0076] 2) Accurately pipette 8.2 mL of 0.5 mol / L Na2CO3 + 5.4 mL of 0.5 mol / L NaHCO3 into the prepared solution above, filter by F membrane (0.45 μm), and sonicate to remove air bubbles (15 min).
[0077] Note: Due to slight differences in instrument performance, the organic phase concentration can be selected in the range of 20% to 30%. The appropriate organic phase concentration can be selected based on the baseline fluctuation (<0.05uS). Since different organic phase concentrations in the mobile phase will have a significant impact on the peak area of lithium salt, the standard curve and the sample must be performed under the same mobile phase conditions during quantification.
[0078] 2.1.4 Preparation and determination of standard curve samples
[0079] 2.1.4.1 Preparation of standard samples
[0080] When the composition of the electrolyte to be tested is unknown, or when there is no standard sample with the same composition as the electrolyte to be tested, DMC is used as a solvent to prepare a mixed standard (hereinafter referred to as "standard sample") with a concentration close to that of the lithium salt and additives to be tested.
[0081] 2.1.4.2 Determination of the standard curve
[0082] Weigh 0.10 g, 0.25 g, and 0.50 g of standard samples (accurate to 0.0001 g), and accurately dilute them with pure water to 50.00 g (accurate to 0.0001 g) in 50 mL volumetric flasks. Record the specific sample weight and the mass after dilution. Let the mass fractions of lithium salts such as LiPF6, LiDFOB, and LiBOB in the standard samples be X1, X2, X3, etc., respectively, then the content of the standard curve series is...
[0083] 2.1.5 Preparation of the test sample
[0084] Accurately weigh 0.25 g (accurate to 0.0001 g) of the sample to be tested, and accurately measure it to 50.00 g (accurate to 0.0001 g) with ultrapure water in a 50 mL volumetric flask; record the specific amount of sample weighed and the mass after dilution.
[0085] 2.1.6 Sample Measurement
[0086] 2.1.6.1 Following the operating procedures of the Dionex ion chromatograph, set the flow rate to 1.0 mL / min, rinse the system with eluent until the instrument is running stably, set the instrument mode, run time to 75 min, and injection volume to 1.5 mL, and test the standard and the sample to be tested.
[0087] 2.1.7 Results Presentation
[0088] Plot a standard curve with the peak areas of LiPF6, LiDFOB, LiBOB… in the standard sample as the x-axis and the content as the y-axis, and obtain the linear equation Y = AX + B(R) for the analyte. 2 >0.997), and calculate the concentrations of LiPF6, LiDFOB, LiBOB... in the sample based on the linear equation.
[0089]
[0090] X0: Peak area of each lithium salt or additive in the sample to be tested, uS*min;
[0091] M: The accurate mass of the diluted sample, in g;
[0092] m: Sample mass, g;
[0093] A: The slope corresponding to the standard curve;
[0094] B: The intercept corresponding to the standard curve.
[0095] 2.1.7.1 Note: Standard samples must be prepared and tested immediately.
[0096] 3. Quantitative methods for organic additives such as FEC in electrolytes
[0097] Quantitative analysis of organic additives such as FEC using gas chromatography (GC)
[0098] 3.1 Principle
[0099] Gas chromatography was used, with N2 as the carrier gas, to carry the organic solvents and additives from the electrolyte into the chromatographic column. A KB-200 capillary column was used to separate the solvents and additives, and an FID detector was used for detection. The area percentage was corrected using a one-point calibration method with the preparation of corresponding standard solutions to determine the actual ratio of each solvent and additive in the sample.
[0100] 3.2 Instruments and Reagents
[0101] Gas chromatograph: Agilent 7820A or 7890B;
[0102] Capillary column: KB-200 (60m × 0.32mm × 0.5μm) or a column with equivalent separating power;
[0103] Chromatography workstation;
[0104] Analytical balance (accurate to 0.0001g);
[0105] Reagents: Solvents and additives contained in the electrolyte and mixed solvents (purity ≥ 99.9%).
[0106] 3.3 Instrument Operating Conditions
[0107] Taking the KB-200 column as an example, the column temperature is programmed to rise to 80℃ (hold for 7 min), then rise to 260℃ at a rate of 10℃ / min (hold for 5 min); the injection port temperature is 260℃; the detector temperature is 280℃; the column flow rate is 1.5 mL / min; the split ratio is 50:1; and the injection volume is 0.2 μL.
[0108] 3.4 Standard sample preparation, testing, and correction factor calculation:
[0109] First, prepare a standard sample (referred to as "standard sample") with the same composition as the sample to be tested. Following the above rules, select appropriate conditions to set the instrument parameters. After the instrument stabilizes, repeatedly rinse the 10 μl microsyringe with the standard sample 5-8 times. Then, inject 0.2 μl of the standard sample into the gas chromatograph and calculate the area percentage correction factor F for each component. When replacing the column, the correction factor needs to be re-determined. The correction factor is valid for one year; after one year, a new correction factor must be prepared. The column should not be disassembled during use; the instrument's condition must remain unchanged. F = percentage of substance / percentage of area.
[0110] 3.5 Sample Testing
[0111] Before injection and testing, the samples (finished products and standards) need to be kept at a constant temperature of 25℃ in a constant temperature incubator or cabinet (for 10-15 minutes) before injection and testing. After repeatedly rinsing the microsyringe with the sample to be tested 5-8 times, 0.2μl of the sample to be tested is injected into the gas chromatograph to obtain the uncorrected area percentage of each substance in the sample.
[0112] 3.6 Results Processing: Actual FEC Percentage = Area Percentage × F.
[0113] The lithium-ion battery of this application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, all materials used in the following embodiments and comparative examples are commercially available products.
[0114] Example 1
[0115] This embodiment describes a lithium-ion battery, and its preparation process is as follows:
[0116] Step S10: Weigh out 2% polyvinylidene fluoride, 2% conductive carbon black (Super P) as conductive agent, and 96% positive electrode active material LiCoO2 (LCO) or LiNi by mass percentage. 0.8 Co 0.1 Mn 0.1 (NCM) is added sequentially to N-methylpyrrolidone (NMP) and thoroughly mixed to form a positive electrode slurry. The positive electrode slurry is coated onto an aluminum foil current collector, dried, cold-pressed, and slit to obtain the positive electrode sheet; wherein, the positive electrode active materials are LiCoO2 / LiNi0.8 Co 0.1 Mn 0.1 All are commercially available products;
[0117] Step S20: Weigh 1.5% sodium carboxymethylcellulose (CMC), 2.5% polymerized styrene-butadiene rubber (SBR), 1% Super P, and 95% negative electrode active material according to their mass percentages. The negative electrode active material is a mixed negative electrode active material with a capacity of 420 mAh / g formed by silicon-oxygen composite material and graphite G49. Add the above raw materials to deionized water in sequence, stir and mix thoroughly to form a negative electrode slurry, coat the negative electrode slurry onto a copper foil current collector, dry, cold press, and slit to obtain a negative electrode sheet.
[0118] The silicon-oxygen composite material can be prepared by the following methods:
[0119] a) Preparation of partially lithium-doped silicon oxide: After uniformly mixing silicon oxide with LiH, the mixture is transferred to a crucible and calcined under an inert atmosphere to obtain partially lithium-doped silicon oxide, which is a mixture of lithium silicate and silicon oxide.
[0120] b) In-situ synthesis of non-lithium silicates: After uniformly mixing partially lithium-doped silicon oxide and magnesium salt, the mixture is calcined under an inert atmosphere to generate non-lithium silicates in situ on the surface of partially lithium-doped silicon oxide.
[0121] c) Secondary coating of carbonaceous materials: The composite material synthesized in step b is placed in an inert atmosphere furnace, and an organic carbon source gas is introduced. A pyrolysis reaction occurs at a high temperature, thereby forming a carbonaceous coating layer on the surface of the lithium-doped silicon oxide composite material, and the silicon-oxygen composite material used in the embodiments of this application is obtained.
[0122] Step S30: The positive electrode sheet, negative electrode sheet and commercial polyethylene separator prepared above are used to make a battery cell, which is packaged with polymer packaging film, filled with electrolyte, and processed by formation and other processes to make a 4Ah soft-pack lithium secondary battery.
[0123] The specific preparation process of the electrolyte in this embodiment is as follows:
[0124] Ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 1:1:1. Lithium hexafluorophosphate (LiPF6) was then added to the resulting mixture until the molar concentration was 1 mol / L. Different types and amounts of additives were then added. The specific types and amounts of additives are listed in Table 1.
[0125] Examples 2-33 and Comparative Examples 1-7 were carried out according to the method of Example 1. The difference was that the ratio 'a' of Li2SiO3 and Li2Si2O5, which are high-efficiency silicon materials in the positive and negative electrode active materials of the lithium-ion battery, was different, as were the types and contents of electrolytes added. The details are shown in Table 1.
[0126] The cycle performance and storage performance of lithium-ion batteries from different embodiments and comparative examples were tested, and the test results are listed in Table 1. The specific test methods for the cycle performance and storage performance of the lithium-ion batteries are as follows:
[0127] 1. Cyclic performance test:
[0128] The lithium-ion batteries prepared in each embodiment and comparative example were placed in an oven at a constant temperature of 25±3℃ and charged at a constant current of 1C to 4.45V (for lithium-ion batteries with LCO positive electrode active material) or 4.3V (for lithium-ion batteries with NCM positive electrode active material). Then, they were charged at a constant voltage until the current dropped to 0.05C. Then, they were discharged at a constant current of 1C to 3.0V. This cycle was repeated 500 times. The discharge capacity of the 1st and 500th cycles was recorded. The capacity retention rate after 500 cycles was calculated using the following formula: Capacity retention rate (%) = Discharge capacity of the 500th cycle / Discharge capacity of the 1st cycle × 100%.
[0129] 2. Performance test after 14 days of storage at 60℃:
[0130] Under an ambient temperature of 25±3℃, the lithium-ion battery was charged and discharged once at 0.2C / 0.2C, and the capacity of this charge and discharge cycle was recorded as the initial capacity. The lithium-ion battery was then charged again at a constant current of 0.2C to 4.45V (LCO) or 4.3V (NCM), and then charged at a constant voltage until the current dropped to 0.05C. After charging, the battery was left to stand at 60℃ for 14 days, and then left to stand in open circuit at room temperature for 2 hours. It was then discharged at a constant current of 0.2C to 3.0V, and the remaining capacity was recorded as: remaining capacity / initial capacity × 100%.
[0131] 3. Testing and plotting the film formation potential of lithium-ion batteries:
[0132] Lithium-ion batteries from Example 1 and Comparative Example 1 were charged at 75°C to 3.2V using a 0.05C hot-pressing process. Voltage and capacity data were recorded during the charging process. The capacity was differentiated from the voltage to obtain dQ / dV data. A graph was plotted with voltage on the x-axis and dQ / dV data on the y-axis to obtain... Figure 2 The film formation potential diagram is shown.
[0133] 4. Elemental analysis chart of SEI membrane
[0134] Lithium-ion batteries from Example 1 and Comparative Example 1 were used. Both sets of batteries underwent initial charging using a hot-pressing formation machine, with identical charging steps (current 0.05C, temperature 75℃, cutoff voltage 3.2V). The batteries were disassembled under an Ar atmosphere in a glove box. The negative electrode sheets from both sets of batteries were taken, cleaned with DMC, and dried before preparing samples. XPS tests were performed on the samples, and peak fitting was performed on the XPS test data to obtain... Figure 3 The elemental analysis spectrum of the SEI membrane is shown.
[0135] Table 1
[0136]
[0137]
[0138]
[0139] A comparison of Examples 1-9 and Comparative Example 1 shows that when the values of a and c are fixed, the ratio K of b / a, within the range of 0.005-0.05, exhibits a more significant improvement in cycle performance with a larger K value. This may be because the lithium salt additive reacts with the Li-containing compound before the fluorocarbonate. x Si y O 1+2y The negative electrode of (Li2SiO3 and Li2Si2O5) lithium silicon oxide crystals reacts and passivates its surface, thereby improving the quality of the fluorinated carbonate film on the negative electrode surface. This effectively prevents the alkaline surface of the negative electrode active material from contacting the electrolyte during cycling, reducing the probability of side reactions between the negative electrode and the electrolyte, and thus improving the cycle performance and high-temperature storage performance of lithium-ion batteries.
[0140] Figure 2 The test graphs show the film formation potentials of the lithium-ion batteries corresponding to Example 1 and Comparative Example 1, as shown below. Figure 2 As shown, compared to the electrolyte without lithium salt additives in Comparative Example 1, a new peak appears around 2270 mV in Example 1, indicating that LiDFOB can form a film on the surface of the negative electrode active material before FEC.
[0141] Figure 3The images show the elemental analysis spectra of the SEI films in Example 1 and Comparative Example 1. Before analysis, the lithium-ion batteries after formation or capacity testing can be disassembled, the negative electrode removed, and elemental analysis of the negative electrode surface performed using XPS. Figure 3 As shown, compared with Comparative Example 1, after adding LiDFOB in Example 1, B element was detected on the negative electrode surface, and characteristic peaks of BO and BF appeared in B 1s, indicating that LiDFOB participated in SEI formation and changed the SEI film composition of fluorocarbonate.
[0142] Figure 4 This is a comparison graph of the cycle performance of lithium-ion batteries in Example 9 and Comparative Example 1. Figure 4 As can be seen, the lithium-ion battery corresponding to Example 9 can significantly improve its cycle performance by adding a specific amount of lithium salt additive, such as... Figure 4 As shown, the lithium-ion battery corresponding to Example 9 retains almost no capacity decay after 500 cycles, maintaining a capacity of 92%, while the lithium-ion battery corresponding to Comparative Example 1 retains less than 70% of its capacity after 500 cycles.
[0143] The comparison data between Examples 1-9 and Comparative Example 2 show that when K < 0.005, the lithium salt additive content is too low to effectively passivate Li. x Si y O 1+2y The crystal surface of lithium silicon oxides (Li2SiO3 and Li2Si2O5) results in poor film formation of fluorinated carbonates, which cannot effectively suppress side reactions, has little effect on improving cycle life, and deteriorates storage performance.
[0144] The comparison data between Examples 1-9 and Comparative Examples 3-4 show that when K is too large and exceeds the limit range, it has no effect on improving the performance of lithium-ion batteries. The reason may be that when the K value is too large, the lithium salt additive content is too high, resulting in a passivation film that is too thick and the impedance is too high. Therefore, the polarization of charge and discharge increases, and there is no significant improvement in cycle performance, resulting in poor storage performance.
[0145] The comparative data from Examples 1-9 and Comparative Examples 5-6 show that if no lithium salt additives are added, simply increasing the FEC content has a very limited effect on improving the cycle performance of lithium-ion batteries.
[0146] The test data from Examples 10-28 show that when the value of K is in the range of 0.005 to 0.05, changing the type of lithium salt additive, the content of fluorocarbonate, and the value of L will have a certain impact on the cycle performance and storage performance of lithium-ion batteries. However, compared with the lithium-ion batteries of Comparative Examples 1-6, their cycle performance and storage performance are improved to a certain extent.
[0147] By comparing Examples 29-33 and Comparative Examples 6-7, it can be seen that the relationship between K value and battery performance also applies to the NCM system.
[0148] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a membrane between the positive electrode and the negative electrode, and an electrolyte filled between the positive electrode and the negative electrode; The negative electrode includes a negative electrode active material, which includes lithium silicon oxide compounds Li2SiO3 and Li2Si2O5, and the mass percentage 'a' of the lithium silicon oxide compounds in the negative electrode active material ranges from 30% to 50%. The electrolyte includes additives, including lithium salt additives, which include at least one of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium difluorobis(oxalato)phosphate, or lithium difluorophosphate; the mass percentage b of the lithium salt additive in the electrolyte ranges from 0.6% to 2%. Wherein, the relationship between a and b satisfies: 0.005 ≤ b / a ≤ 0.05; The additive also includes fluorocarbonate, wherein the mass percentage c of the fluorocarbonate in the electrolyte ranges from 5% to 20%, and the relationship between a and c satisfies: 0.05 ≤ c / a ≤ 0.
5.
2. The lithium-ion battery according to claim 1, characterized in that, The fluorocarbonate includes at least one of fluoroethylene carbonate or difluoroethylene carbonate.
3. The lithium-ion battery according to claim 1 or 2, characterized in that, The electrolyte includes an electrolyte, and the molar concentration of the electrolyte in the electrolyte is 0.01 mol / L to 2.0 mol / L.
4. The lithium-ion battery according to claim 1 or 2, characterized in that, The electrolyte also includes sulfur-containing ester compounds and / or nitrile compounds, wherein the sulfur-containing ester compounds constitute 1% to 5% of the electrolyte by mass, and the nitrile compounds constitute 2% to 6% of the electrolyte by mass.
5. A terminal device, characterized in that, It includes an electrical component and a lithium-ion battery as described in any one of claims 1-4, wherein the lithium-ion battery is electrically connected to the electrical component to provide power to the electrical component.
Citation Information
Patent Citations
Negative electrode material, preparation method thereof and lithium ion battery
CN112803015A
Electrochemical device and electronic device comprising same
CN113161601A
